2009
DOI: 10.21608/asat.2009.23441
|View full text |Cite
|
Sign up to set email alerts
|

Wind Tunnel Experiments and CFD Analysis of Blended Wing Body (BWB) Unmanned Aerial Vehicle (UAV) at Mach 0.1 and Mach 0.3

Abstract: This paper discusses the aerodynamics behavior of a baseline design of a Blended Wing Body (BWB) aircraft developed at MARA University of Technology (UiTM). Two methods of analysis are presented, i.e. Steady-state, three-dimensional Computational Fluid Dynamics (CFD) of the BWB at Mach 0.3 and Wind Tunnel experiments on 1/6 scaled half model of the BWB at Mach 0.1. In both methods of analysis, Lift Coefficient (CL), Drag Coefficient (CD) and Pitching Moment Coefficient (CM) are measured and compared at respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The turbulence modeling in transitional flows was obtained using the − SST transitional model. This turbulence model is the most suitable one used in many studies, as observed here [15,16]. Table 3 shows the results of the aerodynamic variables of all the 4 UAV models.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The turbulence modeling in transitional flows was obtained using the − SST transitional model. This turbulence model is the most suitable one used in many studies, as observed here [15,16]. Table 3 shows the results of the aerodynamic variables of all the 4 UAV models.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…One of the most important characteristics that affect flight performance and stability is the aerodynamic shape of the UAV. In the literature, various methods such as computational fluid dynamics (CFD) and wind tunnel (WT) are used to determine the aerodynamic shape (Acree and Johnson, 2006;Wisnoe et al, 2009;Yeo and Johnson, 2009;Mariens, 2012). In their studies which these methods are used, the maximum value of lift/drag ratio (E max ) that significantly influences flight performance is often preferred (Beechook and Wang, 2013;Smith et al, 2001;Azlin et al, 2011;Bourdin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Wind tunnel test is high-cost and time-consuming, most of all, the results are not accurate in the flight condition of low Reynolds number. And CFD software analysis usually has heavy work on the 3D model meshing, and the gap effect as well as the frictional drag is often neglected [ 4 , 5 ]. DATCOM, introduced by the US Air Force, is another choice for the parameter calculation.…”
Section: Introductionmentioning
confidence: 99%